PERAN GURU SEBAGAI PELAKSANA LAYANANBIMBINGANKONÂ¬SELING DALAM MEMBANGUNSIKAP DISIPLINSISWA DI SDNEGERI KEPUTRAN2 YOGYAKARTA TAHUNAJARAN2015/2016 - Umi Larasati; FX Sindhuredja (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
The research aims to get how the teacherâ€™s role as guidance and counseling service in establishing the discipline of students at SD Negeri 2 Keputran Yogyakarta year 2015/2016. The kind of the research is qualitative descriptive, using interviews, observation, and documentation for collected data. The subject of the research are headmaster, teachers, and students. The technique of data analysis uses interactive model are data collection, data reduction, data display, and conclusion drawing/verification. The result of this research indicated that: 1) the role of the teacher as an guidance counseling services among others, as counselors, facilitators, and collaborators; 2) some examples of activities that created the teacher as an effort to build the discipline of students, among others, the flag ceremony every Monday and other major holidays, infaq routine once a week, morning assembly, pray, picket class, the working group; and 3) the constraints faced by teachers in an effort to build the discipline of students can be seen in terms of students, guardians or parents, and teachers.